(untitled) (Revista Puertorriqueña de Psicologia, 2019)
Depersonalization is a common psychiatric symptom that remains understudied amongst Latino/Hispanic populations. There is evidence that depersonalization is relatively common among persons with a history of psychological trauma and interpersonal abuse. In this study we compared the frequency of depersonalization experiences in two group of adults: 40 patients with a history of interpersonal abuse (HIA), and a control community group (CCG) of 40 adults without HIA. Results indicated that the patients with HIA showed significantly higher scores on the Cambridge Depersonalization Scale (CDS). Moreover, 25% of the HIA group (vs. none of the CCG) obtained a score (>70) in the CDS that suggests the presence of a Depersonalization Disorder. Moreover, as the frequency of abusive experiences increased, the scores on the CDS concomitantly increased, in many cases to clinical levels. Consistent with other international studies, we found a significant correlation between depersonalization and depressive symptoms as measured with the Patient Health Questionnaire-9. Results are consistent with the assertion that interpersonal abuse is intricately related with depersonalization and dissociative symptoms.